Neoadjuvant chemotherapy induces breast cancer metastasis through a TMEM-mediated mechanism - Karagiannis, George S; Pastoriza, Jessica M; Wang, Yarong; Harney, Allison S; Entenberg, David; Pignatelli, Jeanine; Sharma, Ved P; Xue, Emily A; Cheng, Esther; D'Alfonso, Timothy M; Jones, Joan G; Anampa, Jesus; et al. (Science translational medicine, 2017)
Breast cancer cells disseminate through TIE2/MENA /MENA -dependent cancer cell intravasation sites, called tumor microenvironment of metastasis (TMEM), which are clinically validated as prognostic markers of metastasis in breast cancer patients. Using fixed tissue and intravital imaging of a PyMT murine model and patient-derived xenografts, we show that chemotherapy increases the density and activity of TMEM sites and Mena expression and promotes distant metastasis. Moreover, in the residual breast cancers of patients treated with neoadjuvant paclitaxel after doxorubicin plus cyclophosphamide, TMEM score and its mechanistically connected MENA isoform expression pattern were both increased, suggesting that chemotherapy, despite decreasing tumor size, increases the risk of metastatic dissemination. Chemotherapy-induced TMEM activity and cancer cell dissemination were reversed by either administration of the TIE2 inhibitor rebastinib or knockdown of the gene. Our results indicate that TMEM score increases and MENA isoform expression pattern changes with chemotherapy and can be used in predicting prometastatic changes in response to chemotherapy. Furthermore, inhibitors of TMEM function may improve clinical benefits of chemotherapy in the neoadjuvant setting or in metastatic disease.